STRATEGI KEPEMIMPINAN PENDIDIKAN BERBASIS DATA DALAM PENINGKATAN MUTU MANAJEMEN PEMBIAYAAN LEMBAGA PENDIDIKAN DI MADRASAH - Fatmah Nur’aeni; Wifdatun Nisa; Siswadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine data-driven educational leadership strategies in improving the quality of education financing management in madrasah. The research employs a qualitative approach using library research by analyzing relevant literature from scientific journals, books, and international institutional reports. The findings reveal that data-driven educational leadership plays a crucial role in enhancing the effectiveness, efficiency, transparency, and accountability of financial management in educational institutions. Through the utilization of data, educational leaders, particularly madrasah principals, are able to formulate more targeted budgeting policies, prioritize resource allocation based on actual needs, and conduct measurable, indicator-based evaluations. However, the implementation of data-driven leadership strategies in education financing management still faces several challenges, especially in newly established and Islamic-based educational institutions such as madrasah. These challenges include limited human resources with data literacy skills, low technological capacity, and inadequate financial information system infrastructure. In addition, organizational culture that is not yet adaptive to data-based decision-making also becomes a significant barrier. Therefore, adaptive and strategic leadership efforts are required, including strengthening human resource capacity, gradually developing technology-based financial systems, and fostering a data-driven organizational culture. Moreover, the integration of Islamic values such as transparency, accountability, and trustworthiness (amanah) becomes an essential foundation in implementing data-driven leadership in madrasah. Thus, data-driven educational leadership in financing management can serve as a strategic approach to sustainably improve the quality of financial governance and overall educational quality in madrasah.